1999
DOI: 10.1123/jtpe.19.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sequential Feedback on Preservice Teacher Instructional Interactions and Students’ Skill Practice

Abstract: This study, conducted within an undergraduate Methods of Teaching Physical Education and School-Based Practice Teaching course, used an AB maintenance-across-participants design to (a) sequentially describe preservice teachers’ (N = 4) instructional interactions with students, (b) examine the effects of sequential feedback on the sequential nature of preservice teachers’ instructional interactions with students, and (c) assess the influence of differential sequential preservice teacher instructional interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
1
0
4
Order By: Relevance
“…Ten studies involved information feedback compared with praise or corrective feedback. Four of seven studies confirmed that providing individual information feedback has more beneficial effects on students’ volleyball [ 35 ], tossing [ 20 ], cup-stacking [ 34 ], and skill practice [ 31 ] than praise or corrective feedback. By contrast, three studies found no significant differences in students’ lacrosse [ 15 ], volleyball [ 16 ], and cup-stacking skills [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies involved information feedback compared with praise or corrective feedback. Four of seven studies confirmed that providing individual information feedback has more beneficial effects on students’ volleyball [ 35 ], tossing [ 20 ], cup-stacking [ 34 ], and skill practice [ 31 ] than praise or corrective feedback. By contrast, three studies found no significant differences in students’ lacrosse [ 15 ], volleyball [ 16 ], and cup-stacking skills [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Öğretim elemanlarını değerlendirme ölçeğinden elde edilen diğer bir önemli bulgu ise "Öğretim elemanlarının derste güçlük çeken öğrencilere istekli bir şekilde yardımcı olmalarıdır" (4.02). Bu konuda yapılmış çalışmalar, öğretmenlerin yardım ve pozitif yaklaşımlarının öğrenciyi etkili bir öğrenme ortamına sokarak motivasyonlarını yükselttiği, kendilerine güvenlerini yükselttiği yönündedir (32,33).…”
Section: Tartişma Ve Sonuçunclassified
“…Bu konuda yapılmış çalışmalar, öğretmenlerin pozitif yaklaşımlarının öğrenciyi etkili bir öğrenme ortamına sokarak motivasyonlarını yükselttiği, kendilerine güvenlerini yükselttiği yönündedir. (6,7,10).…”
Section: Tartişma Ve Sonuçunclassified
“…Anlık geri bildirimlerin sonradan yapılan geri bildirimlere göre daha etkili olduğu ve daha sonra aynı problemle karşılaşıldığında hata yapma olasılığının düşük olduğu Benette ve Cavanough (14) tarafından belirtilmiştir. Bunun yanı sıra öğrencinin doğru yanlış ve eksiklerinin bildirilmesi ve düzeltilmeye yönelik geri bildirimlerin yapılması, onların performansını arttırdığı ve motivasyonunu yükselttiği yönünde pek çok araştırma sonucu bu çalışmanın sonuçlarını da desteklemektedir (2,6,8,13,14,15). Çalışmada öğretmenler "iletişimde açık ve anlaşılır bir biçimde bilgi verici olmalıdır ayrıca sözsüz iletişimi iyi olmalıdır" görüşüne tamamen katılmışlardır.…”
Section: Tartişma Ve Sonuçunclassified
See 1 more Smart Citation